Celestial mechanics: new discoveries and challenges for space exploration - Pires, Pryscilla M.; de Melo, Cristiano Fiorilo; Zanardi, Maria Cecília F. P. S. [UNESP]; Winter, Silvia M. Giuliatti [UNESP] (Springer Nature, 2023)
This special issue entitled “Celestial Mechanics: New Discoveries and Challenges for Space Exploration” presents a series of 27 contributions. Some of them are devoted to the analysis of periodic orbits in the solar system and methods for identifying chaos in non-linear dynamical systems. The topic of satellite attitude determination is also covered, as well as a study of orbital manoeuvres around a large body such as Titania. Researches on near-Earth asteroids are also presented, such as transfers to orbits around the Moon for space mining; prevention of a collision of the asteroid Apophis with the Earth and a dynamical study of a disc of particles around Apophis; the dynamical evolution, fates and lifetimes, besides orbital inclination evolution of current large Near Earth Objects (NEOs). Aerospace engineering is explored through the study of periodic lift and drag on the orbit of rectangular parallelepiped satellites, and also the analysis of orbits of a satellite observing the Earth. Further theoretical work concerned the application of the theory of functional connections via the change of variables and the analysis of the linear stability of a tether system using its Hamiltonian function is analyzed in this paper. Since the number of artificial debris in the near-Earth space has increased in the last decade, this topic has become a current problem, thus discussed in details. Solar sails were also researched in detail in this special issue, for example how solar sails can help with lunar flyby maneuvers. Finally, methods for investigating extra solar planetary systems were also applied.